Demands for Grants of Planning Commission 1967-68 (May 1967) - Planning Commission (Planning Commission Government of India, 1962)
The document on the Demand for Grants by the Planning Commission outlines the budgetary requirements for committees and programs engaged in national development, research, and rural planning. Key components include the Research Programme Committee, Committee on Plan Projects, Rural Industries Planning Committee, Programme Evaluation Organization, and the Electronic Computer Unit, with the establishment of the Joint Technical Group on Transport Planning reflecting increased activity in the transport sector. The financial overview for 1965-66 to 1967-68 highlights significant allocations for public cooperation schemes, research programs, and salaries for senior officials. The report emphasizes strategic priorities such as rural development and transport infrastructure while ensuring accountability through program evaluations. Overall, the document presents a comprehensive framework for resource allocation, demonstrating the Planning Commission’s commitment to effective planning, economic growth, and responsive fiscal management.
Planning Commission
Keywords: Planning Commission; Demand for Grants; Budget Allocation; Economic Development; Rural Planning; Research Programs; Transport Planning; Programme Evaluation; Salaries and Establishment; Financial Overview; Strategic Priorities; Fiscal Accountability